COMMUNITY SERVICE HEALTH EDUCATION ABOUT CONSCIOUS EXAMINATION AS EARLY DETECTION OF BREAST CANCER ON THE KNOWLEDGE AND ATTITUDES OF ADOLESCENT GIRLS IN LADANG BAMBU VILLAGE - Dwi Ris Hasanah; Suriati Lubis; Nelly Rahayu (Jurnal Masyarakat Indonesia (Jumas), 2024)
Breast cancer is one of the serious health threats for women, and early detection through breast self-examination (SADARI) plays a crucial role in reducing the mortality rate. Adolescent girls' lack of understanding and skills regarding SADARI techniques is often an obstacle in efforts to prevent breast cancer from an early age. This community service activity aims to increase the knowledge and attitudes of young women in Ladang Bambu Village regarding the importance of SADARI as an early detection step. The program will be carried out on May 21, 2024 through health counseling methods and interactive SADARI practice demonstrations. The results of the evaluation showed a significant increase in knowledge and readiness of the attitude of young women in conducting routine and independent examinations. This education is expected to form sustainable preventive behavior in maintaining the reproductive health of adolescent girls.